2020
DOI: 10.1016/j.applanim.2020.105025
|View full text |Cite
|
Sign up to set email alerts
|

Investigating putative depression-like states in the domestic dog: Does greater time spent displaying waking inactivity in the home kennel co-vary with negative judgment of ambiguity?

Abstract: Investigating putative depression-like states in the domestic dog: does greater time spent displaying waking inactivity in the home kennel co-vary with negative judgment of ambiguity?Harvey, ND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Instead of active behaviour such as moving or standing, lying inactive but awake can also be an expression of continuous restlessness and alertness [ 53 ] which especially during the night alerts on adaptation problems and may impede welfare if proceeding on the long term. Although a problem with sleeping is a symptom of clinical depression in humans [ 54 ], studies in sheltered dogs show that ‘quiet wakefulness’ during the day was not associated with depression-like characteristics [ 55 , 56 ]. The underlying motivations and interpretation of ‘quiet wakefulness’ are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of active behaviour such as moving or standing, lying inactive but awake can also be an expression of continuous restlessness and alertness [ 53 ] which especially during the night alerts on adaptation problems and may impede welfare if proceeding on the long term. Although a problem with sleeping is a symptom of clinical depression in humans [ 54 ], studies in sheltered dogs show that ‘quiet wakefulness’ during the day was not associated with depression-like characteristics [ 55 , 56 ]. The underlying motivations and interpretation of ‘quiet wakefulness’ are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Walker and colleagues [ 34 ] applied a spatial JBT to sheltered dogs and noticed that separation from their kennel-mate did not induce a pessimistic mood. More broadly, with regards the relationship between welfare state and judgment bias in sheltered dogs, Owczarczak-Garstecka and colleagues [ 35 ] found that the percentage of time spent asleep during the night was not predicted by dogs’ optimistic/pessimistic bias, while Harvey and colleagues [ 36 ] found that a more pessimistic judgment bias was unrelated to the amount of time dogs were awake, but inactive, in the home environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the test phase, the dog is presented with ambiguous stimuli over a series of trials, in this case, a bowl in one of three positions between the far right ‘Positive’ and far-left ‘Negative’ positions; either ‘Near Negative’ (NN), ‘Middle’ (M) or ‘Near Positive’ (NP). The dog’s latency to approach these ambiguous stimuli has been widely used as a measure of that dog’s affective state (e.g., Burani et al 2020 ; Burman et al 2011 ; Gruen et al 2019 ; Karagiannis et al 2015 ; Mendl et al 2010 ; Müller et al 2012 ; Wells et al 2017 and Willen et al 2019 who used the five bowl protocol as described above, and Duranton and Horowitz 2019 ; Kis et al 2015 and Harvey et al 2020 who used a modified protocol with M as the only ambiguous location). If the dog is faster to approach the ambiguous bowl, it indicates a positive judgement bias (more “optimistic”), whereas a slower approach suggests a negative judgement bias (more “pessimistic”).…”
Section: Introductionmentioning
confidence: 99%